Evaluation of acute toxicity induced by supercritical carbon dioxide extract of Canarium odontophyllum (CO) Miq. pulp oil in SPF Sprague Dawley rats - Abdul Manap, Nurdiyana; Azlan, Azrina; Hamzah, Hazilawati; Fakurazi, Sharida; Abdul Kadir, Noor Atiqah Aizan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Different solvents extraction was used to extract the good fatty acid composition of Dabai fruits. Nevertheless, solvents extraction may exhibit harmful effects. The present study was aimed to evaluate the safety of using supercritical carbon dioxide extraction (SCO2) of dabai pulp oil by acute toxicity study in Specific Pathogen Free (SPF) Sprague-Dawley (SD) rats. Methods: The CO pulp oil extract was prepared by SCO2 extraction of the freeze-dried pulp and was administered orally to SPF SD rats (consisted of 5 rats/sex/group) at upper limit dose 5000 mg/kg body weight (BW) for 14 days. The study includes the control and treatment groups, each consisting of 5 male and female rats. The rats were fed and allowed to drink sterilized water ad libitum. Fatty acid composition (FAC) of the extract was determined using GC-FID. Electrolytes and biochemical parameters in blood, as well as relative organs weight were measured. Results: The extract at a single dose of 5000 mg/kg did not cause any acute toxicity effects or mortality to the treatment of rats during observation periods in 14 days. FAC of the SCO2 extracted oil exhibited high content of palmitic and linoleic acids. The relative organs weights (ROW) and histopathology of rats were within normal range. Conclusion: Thus, the LD50 was estimated to be more than 5000 mg/kg of CO pulp oil extract and can be considered for further investigation for its therapeutic efficacy in a larger animal model.